MENINGKATKAN HASIL BELAJAR MEMBACA BAHASA INGGRIS SISWA KELAS X.IPA B SMAN 2 MUARA ENIM MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH PADA MATERI TEKS NARATIF - Oktavia Zahara (Pusat Studi Pendidikan dan Kreativitas Guru, 2018)
This study aims to improve the learning outcomes of studentsreading class X. IPA. B SMA Negeri 2 Muara Enim Semester Odd AcademicYear 2016/2017 on English reading subjects Narrative Text using cooperativetype learning model Make a Match. This study is a classroom action researchconsisting of two cycles. Each cycle consists of planning, implementation, action,observation and reflection. The subjects of this study were students of classX. IPA. B as many as 36 students consisting of 27 female students and 9 malestudents. Data collection is done by performing tests and observations. Based onthe data analysis of learning outcomes a